2015
DOI: 10.18517/ijaseit.5.5.563
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Analysis of Land Use Change for 11 years (2004-2014) in Sub-Watershed Sumpur Singkarak

Abstract: The pressure of population growth and the economy has an impact on changes in land use in Sub-watershed Sumpur Singkarak West Sumatra, Indonesia. Changes in land use are analyzed spatially and temporally using satellite imagery Landsat TM 7 and 8 (resolution 30 m) that has been in the interpretation of 2004 to 2014. The analysis is done by comparing the changes in land use in the area of forest, farming and settlement. From the analysis it can be concluded that there has been a decline in forest area of 128 ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Land change has become a serious problem throughout the world (Rozario et al, 2017;Yang et al, 2014;Mondal et al, 2016), impact on a serious threat to environmental sustainability (Fearnside, Kamusako et al, 2009). Rapid land use change has occurred in many parts of Indonesia (Rafiudin et al, 2016;Edwin et al, 2015). This condition results in a negative impact on the status of environmental sustainability, where the serious threat of environmental degradation is certain to occur in the next few years (Adrianto et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Land change has become a serious problem throughout the world (Rozario et al, 2017;Yang et al, 2014;Mondal et al, 2016), impact on a serious threat to environmental sustainability (Fearnside, Kamusako et al, 2009). Rapid land use change has occurred in many parts of Indonesia (Rafiudin et al, 2016;Edwin et al, 2015). This condition results in a negative impact on the status of environmental sustainability, where the serious threat of environmental degradation is certain to occur in the next few years (Adrianto et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The used of remote sensing data satellite has been successfully proof to detect urbanization within land cover distribution (Edwin et al, 2015;Windusari et al, 2017) or urban thermal status (Van et al, 2015), however there are few researchers that explore connectivity of the observe LST temperature (Ts) and air temperature (Ta) before applied to the image data for further analysis. The urbanization impact to the urban thermal environment is quantify by measuring the urban thermal surfaces and the near surface atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in land use were analyzed spatial and temporal changes in land use of forest, farming and settlement using satellite imagery Landsat TM 7 and 8 (resolution 30 m) that has been in the interpretation of 2004 to 2014 [2]. This study concluded that there had been a decline in the forest area of 128 ha (1.6%), an increase in the mixed-farming area of 146 ha (16.1%), an increase in settlement area of 143 ha (26%) for 11 years in Sub-watershed.…”
Section: Introductionmentioning
confidence: 99%